An Analysis of Synonym in the Song Lyrics “Perfect” by Ed Sheeran: A Lexical Semantics Study - Santun Saniora Tamba; Bernieke Anggita Ristia Damanik (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study explores how synonymity is applied in the lyrics of Ed Sheeran's song "Perfect" through a lens of lexical semantics. The main goal of this research is to identify synonymous words and expressions within the lyrics and assess their impact on meaning and emotional depth. A descriptive qualitative methodology is utilized, focusing on the examination of terms and phrases that share similar meanings in the context of the song. For data collection, relevant lexical selections from the lyrics were recorded and categorized based on their semantic relationships. The results indicate that the employment of synonyms enriches the lyrical experience, avoids repetition, and underscores different aspects of love and connection. Additionally, the inclusion of synonymous expressions enhances both the artistic and poetic elements of the song, rendering it more powerful and attractive to listeners. The findings also imply that synonyms are context-dependent and cannot always be used interchangeably without changing the intended message. Therefore, this research underscores the importance of lexical semantics in understanding how language is creatively deployed in song lyrics to articulate complex emotions and convey ideas.